Government Policy Contradictions and Their Impact on Lake Tempe Fishermen: A Case Study of Pallawang and Pakkajalalla - Azisan, Azisan; M.Z, Lukman; Tamma, Sukri; Ariana, Ariana (Journal Public Policy, 2024)
This research aims to evaluate the government policies implemented by Wajo Regency in resolving the complex challenges encountered by the Lake Tempe fishermen. It is difficult to determine the core cause of the Lake Tempe conflict because there are various local terms and interpretations from many researchers with diverse backgrounds. Therefore, this article seeks to provide a more detailed description of the conflict chronology as well as many of the terms used in Lake Tempe studies. This study gathered academic journals, scholarly literature, and related sources using a narrative review technique. The findings from all the articles are interpreted, summarized, and elaborated in a descriptive manner using implementation and evaluation concepts. Through the analysis of the collected data, the research findings reveal that the Wajo Regency administration issued particular regulations to control fisheries resource management to resolve the discrepancies between Pallawang and Pakkajalalla fishermen. The objective was to promote stability while empowering the community to manage fishing resources. However, the regulation's implementation was ineffective because of the limited availability of specialized human resources in the fisheries department, which hindered the successful execution of the policy. Furthermore, it shows that the enacted regulations contradict each other in terms of policy coherence. While the first issue concerns the fishing method, it has now evolved into a problem for the government to solve between the fisheries and agriculture sectors